2002
DOI: 10.1046/j.1365-2923.2002.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Concept mapping assessment in medical education: a comparison of two scoring systems

Abstract: These data suggest that scoring systems for evaluating concept maps in postgraduate medical education may need to account for structural features of maps, if scores are to reflect changes in the developing knowledge frameworks of resident doctors. More research to further evaluate reliability and validity is critical prior to any future use of concept mapping assessment in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 12 publications
(26 reference statements)
5
93
0
10
Order By: Relevance
“…Maps have been used and continue to be used across the education spectrum from elementary to graduate school. Research indicated that the maps are effective in fostering meaningful learning (Al-Kunifreed & Wandersee, 1990;Garcia, 2010;Novak & Gowin, 1984;Novak & Wandersee, 1990;Silesky & Badilla, 2008;Tarte, 2006), assessing learning (Fischler, et al, 2002;Reiska, 2005;West, Pomeroy, Park, Gerstenberger, & Sandoval, 2000;West, Park, Pomeroy & Sandoval, 2002), promoting curriculum development (Bowen & Meyer, 2008;Edmondson, 1995;Heinze-Fry & Ludwig, 2006;Riesco, Fondón, Alvarez, 2008), developing instructional strategy (Fonseca, Extremina, & Fonseca, 2004, Prabhu, Elmesky, & Czarnocha, 2006, Stoddart, 2006 and teaching specific content. Teaching specific content has been researched in areas such as business, where concept maps were used to teach strategic intent (Fourie & Westhuizen, 2008), entrepreneurial behavior (Kyrö, SeikkulaLeino & Mylläri, 2008), and business planning (Kyrö & Niskanen, 2008).…”
Section: Research Summarymentioning
confidence: 99%
“…Maps have been used and continue to be used across the education spectrum from elementary to graduate school. Research indicated that the maps are effective in fostering meaningful learning (Al-Kunifreed & Wandersee, 1990;Garcia, 2010;Novak & Gowin, 1984;Novak & Wandersee, 1990;Silesky & Badilla, 2008;Tarte, 2006), assessing learning (Fischler, et al, 2002;Reiska, 2005;West, Pomeroy, Park, Gerstenberger, & Sandoval, 2000;West, Park, Pomeroy & Sandoval, 2002), promoting curriculum development (Bowen & Meyer, 2008;Edmondson, 1995;Heinze-Fry & Ludwig, 2006;Riesco, Fondón, Alvarez, 2008), developing instructional strategy (Fonseca, Extremina, & Fonseca, 2004, Prabhu, Elmesky, & Czarnocha, 2006, Stoddart, 2006 and teaching specific content. Teaching specific content has been researched in areas such as business, where concept maps were used to teach strategic intent (Fourie & Westhuizen, 2008), entrepreneurial behavior (Kyrö, SeikkulaLeino & Mylläri, 2008), and business planning (Kyrö & Niskanen, 2008).…”
Section: Research Summarymentioning
confidence: 99%
“…In medical education, studies compared student and instructor concept maps (McGaghie, McCrimmon, Mitchell, Thompson, & Ravitch, 2000), assessed learning in resident physicians (West, Pomeroy, Park, Gerstenberger, & Sandoval, 2000), investigated case-based learning and problem-based learning outcomes using concept maps (Eitel, Kanz, Hortig, & Tesche, 2000), measured students' attitude toward preprepared concept maps in light of their learning style (Laight, 2004), investigated the learning processes of third-year medical students (Torre et al, 2007) and explored concept maps as a method to identify clinical reasoning in medical students and experts (Pottier et al, 2010). Finally, medical education researchers explored both structural and relational scoring formulas for concept maps (West, Park, Pomeroy, & Sandoval, 2002).…”
Section: Expansion and Adaptation (2000-2010)mentioning
confidence: 99%
“…The variation in the results of studies on concept maps and critical thinking in nursing education may be related to the variety of scoring formulas in use. West, Park, Pomeroy, and Sandoval (2002) investigated the use of two scoring models using a relational model and a structural model. A structural formula is based on the map's hierarchical structure, and a relational formula is based not on the structure but on the quality of the individual map components.…”
Section: Future Research Implicationsmentioning
confidence: 99%
“…[3] Medical schools have been changing their educational programs and teaching strategies, at national and international levels, to ensure that students have active responsibility for their learning process and are prepared for life-long, self-directed learning. [4] The effort toward developing active learning was based on the concern, expressed by experienced medical educators, that students memorized facts instead of understanding and applying concepts. [5] Unless there is understanding, students may only commit unassimilated data to short-term memory and no meaningful learning will occur.…”
Section: Introductionmentioning
confidence: 99%